Social representations, environment and health: towards a quality environmental education - Silva de Freitas, Eduardo (O Mundo da Saúde, 2006)
This article is about the adequacy and development of the theory of social representations as a catalyzing element for the field of environmental education. The world, that is essentially the result of human beings productions, has been continuously suffering the consequences of the absence of critical reflections. This affects both the environmental dimension and the health dimension. How can we surpass such obstacles and make possible a pragmatic improvement in the environment where we live and interact, in good environmental and health conditions? This work aims to point out one of these possibilities, defending the idea that studying social representations, which stem from social relations, is an important theoretical foundation in the search and implementation of critical environmental education programs and projects related to individuals and societies daily practices. The ultimate aim is making long demanded social transformations to occur by the improvement of a quality environmental education as a strategy for transforming reality.